2018
DOI: 10.1007/s11011-018-0264-9
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant gallic acid induces anxiolytic-, but not antidepressant-like effect, in streptozotocin-induced diabetes

Abstract: The physiopathology of anxiety or depression related to diabetes is still poorly understood. The treatment with antidepressant drugs is a huge challenge due to theirs adherence low rate and many adverse effects. Thus, the seeking for a better treatment for these associated diseases is of utmost importance. Given that the oxidative stress in different tissues occurs in diabetes and anxiety or depression as well, the antioxidant gallic acid becomes an interesting compound to be investigated. Thus, the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…Streptozotocin (STZ) is the most common drug used in experimental diabetes (Radenkovic et al, 2016). STZ-induced diabetes aggravates anxiety-like behaviors (ALB) (Thorre et al, 1997;Aksu et al, 2012;Tang et al, 2015;Rajashree et al, 2017;Aswar et al, 2017;Pereira et al, 2018;Rahmani et al, 2018;Rajabi et al, 2018), depression-like behaviors (DLB) (da Silva Haeser et al, 2007;Gupta et al, 2014;Aswar et al, 2017;Rebolledo-Solleiro and Fernandez-Guasti, 2018), and cognitive deficits (CD) (Zhou et al, 2015;Sun et al, 2017;Gocmez et al, 2019) in rodents. Hilakivi-Clarke et al (1990) reported that male (Swiss NIH) diabetic mice exhibited less social interaction and more aggressive behaviors in the resident-intruder test.…”
Section: Introductionmentioning
confidence: 99%
“…Streptozotocin (STZ) is the most common drug used in experimental diabetes (Radenkovic et al, 2016). STZ-induced diabetes aggravates anxiety-like behaviors (ALB) (Thorre et al, 1997;Aksu et al, 2012;Tang et al, 2015;Rajashree et al, 2017;Aswar et al, 2017;Pereira et al, 2018;Rahmani et al, 2018;Rajabi et al, 2018), depression-like behaviors (DLB) (da Silva Haeser et al, 2007;Gupta et al, 2014;Aswar et al, 2017;Rebolledo-Solleiro and Fernandez-Guasti, 2018), and cognitive deficits (CD) (Zhou et al, 2015;Sun et al, 2017;Gocmez et al, 2019) in rodents. Hilakivi-Clarke et al (1990) reported that male (Swiss NIH) diabetic mice exhibited less social interaction and more aggressive behaviors in the resident-intruder test.…”
Section: Introductionmentioning
confidence: 99%
“…However, GA administration seems to fix and prevent the damage caused by these conditions, since treatment with GA decreased oxidative stress and improved antioxidant enzyme activity in the hippocampus of rats with MS. Previous studies with GA have demonstrated its neuroprotective effects in a rat model of streptozotocin-induced T2D (Pereira et al, 2018), preventing degeneration and neuronal death of the hippocampus. The neuroprotective effect was associated with the elimination of free radicals, deactivating the enzymes responsible for the production of ROS, and promoting positive regulation of SOD and CAT (Saibabu, Fatima, Khan, & Hameed, 2015;Thyagaraju, 2008).…”
Section: F I G U R Ementioning
confidence: 94%
“…In MS and obesity models, there is evidence that GA improves the plasma concentrations of triglyceride and glucose, as well as a recovery of glucose tolerance and lipid metabolism (Bak et al., 2013; Chao et al., 2014; Dludla et al., 2018; Schimites et al., 2020). In animal models, anxiolytic, antidepressant, and antiepileptic effects have also been observed (Can, Turan, Demir Ozkay, & Ozturk, 2017; Pereira et al., 2018). However, there is still not enough information regarding its impact on the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid treatment was capable to generate an anxiolytic-like activity in the EPM and light-dark transition (LDT) tests, but not antidepressant-like effect in the FST. Also, oxidative stress in the rat hippocampus and prefrontal cortex was reversed with gallic acid via decreasing lipid peroxidation and increasing reduced GSH ( Pereira et al, 2018 ).…”
Section: Natural Compounds and The Affected Pathways In Similar Waysmentioning
confidence: 99%